Prospective pharmacokinetic study of intravenous busulfan in hematopoietic stem cell transplantation in 25 children. (8th February 2014) - Okamoto, Yasuhiro; Nagatoshi, Yoshihisa; Kosaka, Yoshiyuki; Kikuchi, Akira; Kato, Shunichi; Kigasawa, Hisato; Horikoshi, Yasuo; Oda, Megumi; Kaneda, Makoto; Mori, Tetsuya; Mugishima, Hideo; Tsuchida, Masahiro; et al.
Abstract The aim of this study was to prospectively evaluate the PK and safety of ivBU in 25 Japanese children (median age six yr; range, five months–17 yr) as one of a combination of drugs in a pretransplant regimen. The patients had acute leukemia (n = 14), CML (2), JMML (5), solid tumors (2), chronic granulomatous disease (1), or metachromatic leukodystrophy (1). Five different dose schedules were used according to the patient's ABW: <9 kg (1.0 mg/kg), 9 to <16 (1.2 mg/kg), 16–23 (1.1 mg/kg), >23–34 (0.95 mg/kg), and >34 kg of BW (0.8 mg/kg). Each dose was given over two h, and sample blood was drawn at nine or 11 separate points for analysis by gas chromatography–mass spectrometry. The AUC varied from 796 to 1905 μmol min/L, and 19 of the 25 patients (76%) remained within the target range without dose adjustment. Two were diagnosed with engraftment failure. Hepatic VOD developed in four, and only one of these showed high AUC (>1500 μmol min/L). Toxicities did not correlate with the BU level. Our data showed very similar PK to those in previous studies, and these dose schedules are applicable to Japanese children.